Analysis Of Early Warning System In Cold Room Vaccine Storage With Iot System - Aprilina Gayuh Arniningtyas; Andjar Pudji; Endro Yulianto; Latafat Mikayilzade Ali (Jurnal Teknokes, 2023)
Cold room as a cold room for vaccine storage is an environment with a controlled temperature used to maintain and distribute vaccines in optimal conditions. To maintain the vaccine, it is necessary to pay attention to routine temperature monitoring, temperature data management, and prevention of situations that endanger the vaccine. The results of this review are expected to be a reference for researchers and readers with the development of research using the DS B1820 temperature sensor which will analyze the results of the data logger output and linearity at sensitive locations Cold Room with LCD output and equipped with an IoT system web display on a PC for monitoring and alarm. and notification via telegram when there is a change in temperature approaching and outside the range of 2 - 8 ° C so that this can make it easier for officers to monitor the temperature and quality of the vaccine. In the results of the study, temperature graphs and temperature data can be displayed which are recorded in minutes. Temperature measurement with standard tools produces the largest difference of 0.83. The lowest temperature was 2.06℃ and the highest temperature was 8.31℃ as well as telegram notification of early warning (2.58℃), evacuation vaccine (2.31℃), and exposed vaccine (8.6℃).